Effect of wind and structural parameters on across wind load of super high-rise buildings - Singh A.; Mandal S. (My University, 2025)
Designing a super high-rise building requires careful consideration of wind loads. The across wind load plays a critical role for super high-rise buildings. A super high-rise building's across-wind load is highly dependent on wind parameters as well as building parameters. It is still unclear how these parameters affect across wind load. Within a possible practical range, this paper attempts to measure the effect of wind and structural parameters on across wind load of a super high-rise building. The wind parameters considered in this study are exponent of mean velocity profile, turbulence intensity, background peak factor and, peak factor for resonant response. Structural parameters influencing across wind load are also considered, such as natural frequency, and structural damping ratio. An analytical method is employed to evaluate the across wind loads to carry out the study. From the results, it can be concluded that among the structural parameters, natural frequency of the structure is the most dominant parameter for the evaluation of across wind loads. In terms of wind parameters, the exponent of mean wind profile has the most impact on the across wind load. The across wind load is not affected by turbulence intensity. This study assists the designers in determining the most appropriate values for wind and structural parameters while estimating the across wind loads. © 2023 MIM Research Group. All rights reserved.